Pricing effects when competitors arrive: The case of discount certificates in Germany - Schertler, Andrea (Journal of Banking & Finance, 2016)
This article investigates how overpricing of outstanding certificates, also called master certificates, changes when competing products that duplicate the features of master certificates are issued. I argue that competition effects may be reverted and overpricing may increase rather than decrease after competitors arrive, when retail investors fail to detect implications of credit risk differences on certificates’ values. Using difference-in-differences estimations on matched samples, I find that overpricing of master certificates decreases after the competing products have been issued, but only when the master issuer’s credit risk is lower than that of the duplicate issuer, while it increases when the credit risk difference is positive. These findings are robust to controlling for retail investors’ demand in various ways. Thus, the study indicates that retail investors’ failure to detect the value implications of issuers’ credit risk can undermine product competition.